Women, Leadership, and Mosque's Cultures: Indonesian Heritage in New York City - Anwar, Etin (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
This paper examines the use of social, religious and cultural heritage for community building and mosque participation by Indonesian Muslim communities in New York City and its impact on women’s leadership in al-Hikmah mosque and their production of moral agency and pious self in the mosque setting. I argue that Indonesian Muslim women in AI-Hikmah mosque has more leadership capacity due to the cultural heritage of Indonesian Islam and the complementary status of women in their communities. In this paper, I will, first, discuss how the cultural heritage of a mosque along with its patriarchal, masculine leadership influences women's treatment. I will, secondly, examine how female authority is produced within the enmeshed patriarchal leadership, the heritage of Indonesian values. and masculine mosque cultures. In particular, I will discuss how women's religious and social activities generate empirical characters that shape the performance of female moral agency and the cultivation of the pious self. I will, finnally, analyze a pattern of female authority in the mosque and the way in which women construct their authority as leaders in the mosque. Throughout the paper, I draw parallels between female authority in AI-Hikmah mosque and the social and cultural practices in Indonesia.